Improved method for measuring low-concentration radium and its application to the Super-Kamiokande Gadolinium project. (20th September 2020) - Ito, S; Ichimura, K; Takaku, Y; Abe, K; Harada, M; Ikeda, M; Ito, H; Kishimoto, Y; Nakajima, Y; Okada, T; Sekiya, H
Abstract: Chemical extraction using a molecular recognition resin named "Empore Radium Rad Disk" was developed to improve sensitivity for the low concentration of radium (Ra). Compared with the previous method, the extraction process speed was improved by a factor of three and the recovery rate for $^{226}$ Ra was also improved from $81±4%$ to $>99.9%$ . The sensitivity on the $10^{-1}$ mBq level was achieved using a high-purity germanium detector. This improved method was applied to determine $^{226}$ Ra in Gd$_2$ (SO$_4$ )$_3{·}$ 8H$_2$ O which will be used in the Super-Kamiokande Gadolinium project. The improvement and measurement results are reported in this paper.